Mathematical modelling of HIV infection therapy - Hraba, T; Dolezal, J (International journal of immunopharmacology, 1995)
The previously developed mathematical model simulates the CD4+ lymphocyte dynamics in HIV infection very well. As the number of these cells is a good indicator of the infection progression, it was used to evaluate the effectiveness of different therapeutic interventions. For chemotherapy simulation, both permanent and temporary zinovudine (AZT) administration were considered and the induced return of the CD4+ lymphocyte counts was analysed. Similar analysis was performed for active and passive immunotherapy. The model offers also the possibility of stimulating the CD4+ dynamics after depletion of CD8+ lymphocytes by antibodies. Even one simulated administration of anti-CD8 antibodies increases the CD4+ lymphocyte counts and prolongs the survival of the patient. However, if cells involved in protective immunity are assumed to belong to the CD8+ category, anti-CD8 antibodies accelerate the decrease of CD4- cells and thus shorten the patient's survival.
Keywords: Zidovudine; HIV Infections; Lymphocyte Depletion; HIV infekce; lymfocytární deplece; Humans; lidé; CD4-Positive T-Lymphocytes; teoretické modely; zidovudin; CD8-Positive T-Lymphocytes; CD8-pozitivní T-lymfocyty; Models, Theoretical; CD4-pozitivní T-lymfocyty